2015
DOI: 10.1126/scitranslmed.aad3740
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants can increase melanoma metastasis in mice

Abstract: Antioxidants in the diet and supplements are widely used to protect against cancer, but clinical trials with antioxidants do not support this concept. Some trials show that antioxidants actually increase cancer risk and a study in mice showed that antioxidants accelerate the progression of primary lung tumors. However, little is known about the impact of antioxidant supplementation on the progression of other types of cancer, including malignant melanoma. We show that administration of N-acetylcysteine (NAC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
319
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(343 citation statements)
references
References 34 publications
22
319
0
2
Order By: Relevance
“…Melanoma cells show increased dependence on NADPH-generating enzymes in the folate pathway and inhibition of this pathway reduced overt metastasis 34 . In support of this finding, anti-oxidant supplementation increased lymph node metastases but had no effect on the growth of primary tumours 33,34 .…”
Section: Early Colonization Stepsmentioning
confidence: 65%
See 1 more Smart Citation
“…Melanoma cells show increased dependence on NADPH-generating enzymes in the folate pathway and inhibition of this pathway reduced overt metastasis 34 . In support of this finding, anti-oxidant supplementation increased lymph node metastases but had no effect on the growth of primary tumours 33,34 .…”
Section: Early Colonization Stepsmentioning
confidence: 65%
“…To protect themselves during transit, cancer cells associate with platelets 32 and undergo reversible metabolic changes to increase their ability to withstand oxidative stress 33 . Melanoma cells show increased dependence on NADPH-generating enzymes in the folate pathway and inhibition of this pathway reduced overt metastasis 34 .…”
Section: Early Colonization Stepsmentioning
confidence: 99%
“…In this system, antioxidants promoted distant metastasis, while folate pathway inhibition prevented metastasis due to decreased NADPH production, but had no effect on the primary tumor. Similarly, antioxidant treatment increased the number of metastasis in a mouse model of malignanat melanoma, causing increased invasiveness dependent on glutathione synthesis cells (Le Gal et al, 2015). Thus, successful tumors maintain ROS levels within a window that stimulates proliferation without causing cytotoxicity.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…NAC also altered the metabolism marker MCT4 in the tumor stroma of subjects with breast cancer in this trial. These results are important because there is controversy as to whether NAC has anticancer properties since several studies have shown cancer progression 363738 . Also, there is controversy as to what dose of NAC should be used in oncology trials since some advocate using higher doses because of its pharmacokinetics 39 .…”
Section: Discussionmentioning
confidence: 99%